Analisis Sebaran Dampak Pemanfaatan Air Limbah Rumah Sakit ke Formasi Tertentu: Pendekatan Spasial dan Hidrogeologis terhadap Kualitas Airtanah: indonesia - Faisal, Andi Muhammad; Nurmiyanto, Awaluddin; Anggit, Maura (Asian Journal of Innovation and Entrepreneurship, 2025)
This study aims to analyze the impact of hospital wastewater utilization on groundwater quality using secondary data and Modflow visual modeling. This model is used to visualize the spread of contaminants from the effluent of the Wastewater Treatment Plant (IPAL) of Hospital X into the soil, as well as to measure the concentration of wastewater parameters such as TSS, COD, oils and fats, BOD, ammonia, residual chlorine, and fecal coliform at various distances from the source point. The modeling results show that all wastewater parameters meet the established quality standards, with a significant reduction in concentration along the spread distance. The TSS concentration almost reaches 0 (0.01 mg/L) at a distance of 115 meters from the source, while the concentrations of COD, oils and fats, and BOD decrease to 0.25 mg/L, 0.01 mg/L, and 0.02 mg/L at the same distance, respectively. Additionally, ammonia and residual chlorine concentrations are almost undetectable at 115 meters, while fecal coliform also decreases to 0 MPN/100 mL. Based on these results, the utilization of hospital wastewater with the new IPAL system is expected not to have a negative impact on groundwater quality within a certain radius, as the concentration of wastewater parameters continues to decrease with increasing distance from the source.